The Role of Accreditation in Driving Quality Improvement in Higher Education - Ridho, Abdussalam; Julaiha, Siti (Journal of Educational Management Research, 2025)
This study aims to explore the comprehensive process and stages of accreditation in higher education institutions, with particular focus on accreditation as an external quality assurance mechanism. The research also examines strategies to enhance educational quality through institutional accreditation. This paper employs a qualitative approach, utilizing a literature review and document analysis to explore the accreditation process. The study systematically analyzes the stages of preparation, including strengthening the Internal Quality Assurance System (SPMI), digital data management, improving the performance of the tri dharma of higher education, and involving the entire academic community in fostering a quality culture. The findings indicate that accreditation serves not only as an institutional feasibility assessment tool but also as a strategic means to drive continuous improvement. It supports governance enhancement, human resource capacity building, and the development of the tri dharma. The stages of accreditation, from self-evaluation to field assessments and accreditation ranking determination, are critical to institutional progress. This research highlights the importance of accreditation in strengthening higher education institutions' competitiveness, enhancing academic reputation, and ensuring the delivery of high-quality education that adapts to evolving global trends.